Understanding Acupoint Sensitization: A Narrative Review on Phenomena, Potential Mechanism, and Clinical Application. (14th August 2019) - Tan, Huijuan; Tumilty, Steve; Chapple, Cathy; Liu, Lizhou; McDonough, Suzanne; Yin, Haiyan; Yu, Shuguang; Baxter, G. David
Abstract : As part of traditional Chinese medicine, acupoints are considered a dynamic functional area, which can reflect the internal condition of the body. When the body is suffering from disease or injury, corresponding acupoints are believed to be activated and manifest in several sensitized forms, including expansion of the receptive field, pain sensitization, and heat sensitization. Such phenomena are believed to gradually disappear concomitantly with recovery from the disease. Acupoint states are therefore changeable according to health status, a phenomenon known as acupoint sensitization. This review aims to provide an overview of acupoint sensitization based on existing research results and determine priorities for future research. Systematic literature retrieval was conducted in Medline, Embase, Cochrane Library, CINAHL, and AMED from inception to 18 July 2018. Current evidence from research findings to date indicate that acupoint sensitization is based on neurogenic inflammation and that stimulation of sensitized acupoints presents a potential trend of generating a better clinical effect when compared with stimulation of unsensitized points.